Influence of sunlight and oral D3 supplementation on serum 25(OH)D concentration and exercise performance in elite soccer players - Michalczyk, M. M.; Golas, A.; Maszczyk, A.; Kaczka, P.; Zajac, A. (Nutrients, 2020)
The aim of this study was to evaluate the influence of natural sun exposure and six weeks of a high dose of vitamin D supplementation on vitamin D, testosterone and cortisol serum concentrations as well as speed, power and VO2max in professional soccer players. Materials: The study was conducted from January to September. At the beginning of the study, 33 professional soccer players were enrolled; however, only 28 subjects (height 181.5 cm; body mass 77.81 ± 8.8 kg; body fat 12.38% ± 2.4% and muscle mass 40.27 ± 5.3 kg) completed the study. The research consisted of three stages. The first one, lasting 10 days, was conducted in January during a training camp in the south part of Cyprus at a latitude of 34 33°, where participants experienced natural sun exposure; it was called a winter sun exposure (WSE) period. The second stage, which was a supplementation period (SP), lasted 6 weeks, during which all subjects were randomly assigned either to an experimental group—EG (n = 15)—or a placebo group—PG (n = 13)—and were administered 6000 IU/d cholecalciferol or a placebo, respectively. The third stage took place in September, after summertime (summer sun exposure—SSE). The data of the 25(OH)D, free and total testosterone (fT, tT), cortisol as well as 5 and 30 m sprint tests (STs), power of the left leg (PLL) and VO2max were evaluated before and after the WSE period, the SP and SSE. Results: In January, the baseline value of vitamin D in 12 subjects was =20 ng/mL, and 14 of them had levels between 20-30 ng/mL and 2 individuals >30 ng/mL. After the WSE period, significant changes in 25(OH)D, fT, tT and cortisol concentration, as well as in the 5 m ST, were observed. After the SP, in the EG, significant changes were found in 25(OH)D, fT, tT and the 5 m ST. Furthermore, a positive correlation between the concentration of 25(OH) fT and tT was observed. After SSE, 2 out of 28 players had <20 ng/mL 25(OH)D, 12 of them had 25(OH)D between 20 and 30 ng/mL and 14 of them had 25(OH)D between 30 and 50 ng/mL. Significant differences in 25(OH)D, fT, tT concentration and the 5 m ST performance were observed following SSE compared with the WSE period. Conclusion: Due to the serum level of 25(OH)D demonstrated by most participants at the beginning of the study and after summertime, all-year-round supplementation with high doses of vitamin D seems to be a reasonable solution to enhance high 25(OH)D concentration in blood and physical performance. In the middle of the winter, almost half of the soccer players were serum deficient of 25(OH)D. After ten days of sun exposure and 6 weeks of vitamin D supplementation, the concentration of 25(OH)D significantly increased, as did testosterone and results in the 5 m sprint test also improved. Therefore, athletes should be constantly monitored for serum levels of 25(OH)D throughout the year and should be supplemented if deficiencies or insufficient amounts of this vitamin occur.